(untitled) (Nepal Journal of Neuroscience, 2026)
Professor Dr. Dinesh Nath Gongal is revered as one of the greatest pioneers and father figures in the field of surgery and neurosurgery in Nepal. At a time when advanced diagnostic technologies such as CT scans and MRI were not available in the country, he courageously took the historic step of initiating neurosurgical services at Bir Hospital. Introducing such a highly complex specialty under those circumstances required not only exceptional skill and vision, but also immense courage, dedication, and sacrifice. Through unwavering commitment to patient care and the advancement of medicine, he personally arranged and managed surgical instruments and resources, overcoming countless hardships to ensure that neurosurgical services continued without interruption. The strong foundation he built through years of perseverance and selfless service is the reason why Bir Hospital today stands proudly as one of the foremost centers for neurosurgery in Nepal. Beyond his extraordinary clinical contributions, Professor Dr. Gongal also made an immeasurable impact in the academic and educational development of the nation. As the first Vice Chancellor of the National Academy of Medical Sciences (NAMS), he played a historic role in strengthening postgraduate medical education in Nepal. Because of his visionary leadership, dedication, and tireless efforts, hundreds of talented doctors every year have been given the opportunity to pursue higher medical education and specialized training within the country. His contributions have not only shaped individual careers but have also strengthened the entire healthcare system of Nepal. Professor Dr. Dinesh Nath Gongal was not merely a surgeon or an academician; he was a visionary leader, an inspiring teacher, and a guiding light for generations of medical professionals. His lifelong devotion to medicine, education, and humanity has left an indelible mark on the history of Nepalese healthcare. Although his physical presence is no longer among us, his remarkable legacy and invaluable contributions to the medical field will remain forever immortal. His dedication, wisdom, and service to humanity will continue to inspire generations of doctors and healthcare professionals for years to come. He will always be remembered with the deepest respect, gratitude, and admiration. Rajiv Jha MD MS MCh FAANS,FRCS President, Nepalese Society of Neurosurgeons